2020
DOI: 10.1080/02701367.2020.1724861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-Week Cycling Intervention on Successful Aging Measures in Mid-Aged Adults

Abstract: To compare the effect of 12-weeks of cycling training and competition versus recreational cycling on successful aging across physical, psychological, cognitive, and social functioning domains in mid-aged adults. Methods: Recreational cyclists were randomly assigned to an intervention (n = 13, M age = 47.18 years) and comparison (n = 13, M age = 46.91 years) group. Analysis of Covariance was used on self-reported pre-post data to determine changes across time and differences between groups on outcomes. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Given that Masters athletes are often held up as exemplars of successful aging in popular press and research (e.g., [ 68 , 69 , 70 , 71 , 72 ]), we sought older men’s opinions on Masters athletes and Masters sport. While participants typically regarded Masters sport as a laudable endeavour, most of them viewed it as inappropriate for their individual circumstances, nor realistically influential in personal health-related attitude and behaviour changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that Masters athletes are often held up as exemplars of successful aging in popular press and research (e.g., [ 68 , 69 , 70 , 71 , 72 ]), we sought older men’s opinions on Masters athletes and Masters sport. While participants typically regarded Masters sport as a laudable endeavour, most of them viewed it as inappropriate for their individual circumstances, nor realistically influential in personal health-related attitude and behaviour changes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, by not overly relying on the medicalized aspect of exemplars of aging success, there is opportunity for fewer psychological and emotional challenges when the inevitable biomedical processes associated with aging manifest [ 20 ]. Participants seemed to support this notion with their view of Masters athletes as unrealistic role models, which poses a challenge to claims that Masters athletes are exemplars of aging success found in academic literature and popular press (e.g., [ 68 , 69 , 70 , 71 , 72 ]). As argued by Dionigi and Gard [ 25 ] and Gard et al [ 21 ], the concept of Masters athletes as exemplars of successful aging is grounded on problematic ‘sport for all’ policies based on highly individualised assumptions about self-responsibility for health, which ignore social determinants of health and aging, demonise passive leisure, and disregard multiple ways of aging well.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Geard et al. 42 used a randomized controlled trial to examine the effect of an exercise intervention on successful aging indicators. Their study showed that 12 weeks of cycling training helped promote greater social and physical functioning among middle-aged adults aged 40 years and older.…”
Section: Discussionmentioning
confidence: 99%